2009
DOI: 10.1098/rspb.2009.1831
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory interneurons of the human prefrontal cortex display conserved evolution of the phenotype and related genes

Abstract: Inhibitory interneurons participate in local processing circuits, playing a central role in executive cognitive functions of the prefrontal cortex. Although humans differ from other primates in a number of cognitive domains, it is not currently known whether the interneuron system has changed in the course of primate evolution leading to our species. In this study, we examined the distribution of different interneuron subtypes in the prefrontal cortex of anthropoid primates as revealed by immunohistochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 71 publications
10
36
0
Order By: Relevance
“…Use of this approach to quantify the major cell types in the brain can complement and significantly increase the value of studies that use modern molecular or neurochemical labeling techniques to estimate ratios of specific subtypes of cells within a population. Examples of previous studies that used similar approaches include reports showing that inhibitory neurons represent 20–30% of all neurons in the mammalian neocortex and in the frontal cortex of humans they make up approximately 21% of the neuronal population (Hornung and De Tribolet, 1994; Kalus and Senitz, 1996; Benes et al, 2001; Sherwood et al, 2010). These approaches are especially suited for the quantification and comparison of cell types between different cortical areas and brain nuclei.…”
Section: Anticipated Results and Discussionmentioning
confidence: 99%
“…Use of this approach to quantify the major cell types in the brain can complement and significantly increase the value of studies that use modern molecular or neurochemical labeling techniques to estimate ratios of specific subtypes of cells within a population. Examples of previous studies that used similar approaches include reports showing that inhibitory neurons represent 20–30% of all neurons in the mammalian neocortex and in the frontal cortex of humans they make up approximately 21% of the neuronal population (Hornung and De Tribolet, 1994; Kalus and Senitz, 1996; Benes et al, 2001; Sherwood et al, 2010). These approaches are especially suited for the quantification and comparison of cell types between different cortical areas and brain nuclei.…”
Section: Anticipated Results and Discussionmentioning
confidence: 99%
“…Through comparative analyses, we can begin to further understand how the function of specialized cells contributes to interspecific variation in cognitive abilities. Previous research, however, has not found differences in inhibitory interneuron numbers or their distribution in cortical areas, including BA 9, BA 4, BA 32, and BA 44, between humans and anthropoid primates [Sherwood et al, 2010]. The conserved phenotype displayed by inhibitory interneurons in the cortex suggests instead that other genetic and regulatory mechanisms contribute to differences in functional regulation of pyramidal cells by inhibitory interneurons.…”
Section: Beyond Pyramidal Neurons: Inhibitory Interneurons In the Cortexmentioning
confidence: 97%
“…In the primate cerebral cortex, approximately 15-30% of neurons are inhibitory, GABAergic interneurons [DeFelipe, 1997; Sherwood et al, 2010]. Inhibitory interneurons of the cerebral cortex serve an important role in modulating excitatory neuronal function, including control of rhythmic oscillations across assemblages of pyramidal neurons [DeFelipe, 1997] important for the regulation of spike-timing dependent synaptic plasticity.…”
Section: Beyond Pyramidal Neurons: Inhibitory Interneurons In the Cortexmentioning
confidence: 99%
“…In the mouse, a subset of cortical interneurons can be identified by the expression of the ionotropic serotonergic receptor subtype, 5-hydroxytryptamine 3A (5-HT 3A R), and this subgroup overlaps with the previously-identified CR subset (Lee et al, 2010; Rudy et al, 2011; Vucurovic et al, 2010). Interneurons in the primate neocortex, likewise, have been subdivided into three neurochemically-distinct groups that contain PV, CR, or another calcium-binding protein calbindin (CB) (Carder et al, 1996; Conde et al, 1994; DeFelipe, 1997; Gabbott et al, 1997; Glezer et al, 1993; Sherwood et al, 2007, 2010; Zaitsev et al, 2009). The presence of 5-HT 3A R in human interneurons has not been reported.…”
Section: Introductionmentioning
confidence: 99%